2020
DOI: 10.1007/s11882-020-00955-z
|View full text |Cite
|
Sign up to set email alerts
|

Update on DNA-Double Strand Break Repair Defects in Combined Primary Immunodeficiency

Abstract: Purpose of Review The most serious DNA damage, DNA double strand breaks (DNA-dsb), leads to mutagenesis, carcinogenesis or apoptosis if left unrepaired. Non-homologous end joining (NHEJ) is the principle repair pathway employed by mammalian cells to repair DNA-dsb. Several proteins are involved in this pathway, defects in which can lead to human disease. This review updates on the most recent information available for the specific diseases associated with the pathway. Recent Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…The radiosensitive status of any patient undergoing such treatments should be evaluated as to avoid these pejorative outcomes. Likewise, any patient undergoing HSCT should be evaluated for a possible DNA repair defect and the conditioning regimen attenuated accordingly as to avoid catastrophic outcome following transplantation (83).…”
Section: Discussionmentioning
confidence: 99%
“…The radiosensitive status of any patient undergoing such treatments should be evaluated as to avoid these pejorative outcomes. Likewise, any patient undergoing HSCT should be evaluated for a possible DNA repair defect and the conditioning regimen attenuated accordingly as to avoid catastrophic outcome following transplantation (83).…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not study apoptotic response, impaired survival to IR has been reported for B lymphocytes and resting T cells. Interestingly, particularly B lymphocytes and naïve T cells are diminished in patients with DNA repair deficiencies ( 16 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic defects in ATM lead to ataxia telangiectasia (AT) presenting with combined immunodeficiency, genomic instability with predisposition to cancer, severe cellular sensitivity to IR, and cerebellar degeneration ( 15 ). Individuals affected by inborn DNA repair defects, including AT, often present with lymphopenia, predominantly reduced naïve T cells and B cells, and hypogammaglobinemia ( 16 ). In order to provide adequate treatment to these patients and to minimize DNA damaging diagnostic and treatment procedures, early diagnosis and classification of these diseases is highly important to affected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Two pathways are important to resolve the damage and maintain genome stability following DNA-dsb: homologous recombination and non-homologous end-joining (NHEJ) ( 3 , 4 ). The first one requires an extensive sequence homology between the broken DNA and a donor DNA molecule and entails a templated DNA synthesis as a key step in the repair process.…”
Section: Introductionmentioning
confidence: 99%